Li‐S Batteries: A New Type of Multifunctional Polar Binder: Toward Practical Application of High Energy Lithium Sulfur Batteries (Adv. Mater. 12/2017). Issue 11 (22nd March 2017) - Chen, Wei; Qian, Tao; Xiong, Jie; Xu, Na; Liu, Xuejun; Liu, Jie; Zhou, Jinqiu; Shen, Xiaowei; Yang, Tingzhou; Chen, Yu; Yan, Chenglin
Abstract : A new type of polar binder, by polymerization of hexamethylene diisocyanate with polyethylenimine, is reported in article number 1605160 by Jie Xiong, Chenglin Yan and co‐workers, which is successfully used with commercial sulfur powder cathodes, demonstrating remarkably improved capacity retention. The synthesis of this new binder is of interest for the commercial application of Li‐S batteries.